2021
DOI: 10.3390/app11146361
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Vulnerable Road Users Overtaking Maneuver along the Urban Road

Abstract: This paper discusses driving styles while overtaking a vulnerable road user who moves along the shoulder in urban roads. Based on the data obtained from an experiment in pre-defined conditions (combinations of four main effects: vehicle’s initial speed, lane width of the road, vulnerable road users’ type, and location in the shoulder) with an immersive driving simulator, we analyzed four different driving styles of drivers while approaching and passing the objects. It is shown that drivers took avoidance maneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Researchers (3,9,23) have suggested that when approaching a VRU moving on the shoulder, two strategies can be considered to regulate the vehicle's velocity: flying overtaking (i.e., maintaining or increasing the initial speed) and accelerative overtaking (i.e., decreasing the speed to consider the situation before accelerating to overtake a VRU). Moreover, drivers notice the existence of a VRU and avoid him/her when overtaking (i.e., moving away in the horizontal direction) (3,9) .…”
Section: Definitionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Researchers (3,9,23) have suggested that when approaching a VRU moving on the shoulder, two strategies can be considered to regulate the vehicle's velocity: flying overtaking (i.e., maintaining or increasing the initial speed) and accelerative overtaking (i.e., decreasing the speed to consider the situation before accelerating to overtake a VRU). Moreover, drivers notice the existence of a VRU and avoid him/her when overtaking (i.e., moving away in the horizontal direction) (3,9) .…”
Section: Definitionsmentioning
confidence: 99%
“…In this study, four driving styles of drivers in a normal state were investigated using experimental from an immersive driving simulator (9) (Fig. 7).…”
Section: Analysis Of Driver Behavior Of Different Driver Groups Based...mentioning
confidence: 99%
See 3 more Smart Citations